Exploring the potential of a capability framework as a vision and "sensemaking" tool for leaders of interprofessional education - Brewer, Margo (Informa Healthcare, 2016)
Creating a vision (visioning) and sensemaking have been described as key leadership practices in the leadership literature. A vision provides clarity, motivation, and direction for staff, and is essential particularly in times of significant change. Closely related to visioning is sensemaking (the organisation of stimuli into a framework allowing people to understand, explain, attribute, extrapolate, and predict). The application of these strategies to leadership within the interprofessional field is yet to be scrutinised. This study examines an interprofessional capability framework as a visioning and sensemaking tool for use by leaders within a university health science curriculum. Interviews with 11 faculty members revealed that the framework had been embedded across multiple years and contexts within the curriculum. Furthermore, a range of responses to the framework were evoked in relation to its use to make sense of interprofessional practice and to provide a vision, guide, and focus for faculty. Overall the findings indicate that the framework can function as both a visioning and sensemaking tool.